Do bank characteristics influence the effect of monetary policy on bank risk? - Yener Altunbas; Leonardo Gambacorta; David Marqués-Ibá\~nez (European Central Bank (ECB), 2012)
We analyze whether the impact of monetary policy on bank risk depends upon bank characteristics. We relate the materialization of bank risk during the financial crisis to differences in the monetary policy stance and bank characteristics in the pre-crisis period for a large sample of listed banks operating in the European Union and the United States. We find that the insulation effect produced by capital and liquidity buffers on bank risk was lower for banks operating in countries that, prior to the crisis, experienced a particularly prolonged period of low interest rates.
Keywords: E44; E52; G21; 330; bank characteristics; credit crisis; monetary policy; Risk-taking channel